Celtic marketing: Assessing the authenticity of a never ending story. Issue 1 (January 2014) - McAuley, Andrew; Pervan, Simon
ABSTRACT Many consumers around the world are familiar with Celtic‐related themes having been exposed to them in their consumption practices. Identifying who the Celts were is relatively straightforward as, despite having no language, they have left their impression on the landscape and in artefacts. In this paper, we ask whether there is such a thing as a Celtic Feeling that consumers identify with and marketers can utilize. The authenticity of Celtic Marketing Practice is assessed using indexical and iconic cues, and the pursuit of personal goals as a framework applied to three case studies—Guinness, the Irish Pub Company and the Orkadian jewellery industry. Findings suggest an authenticity to Celtic Marketing in terms of brand positioning and, to a lesser extent, marketing management philosophy. Links are made to place marketing, storytelling and experiential marketing. Copyright © 2013 John Wiley & Sons, Ltd.